2014
DOI: 10.1039/c4ra06116k
|View full text |Cite
|
Sign up to set email alerts
|

Polarizability as a landmark property for fullerene chemistry and materials science

Abstract: The review summarizes data on dipole polarizability of fullerenes and their derivatives, covering the most widespread classes of fullerene-containing molecules (fullerenes, fullerene exohedral derivatives, fullerene dimers, endofullerenes, fullerene ions, and derivatives with ionic bonds).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 242 publications
(377 reference statements)
5
85
0
Order By: Relevance
“…According to these data, all studied structures show great values for static polarizability which is due to many delocalized π-electrons over these molecules. The value of 69.5 Å 3 , calculated at the mentioned level of theory for polarizability of C 60 fullerene, is in satisfactory agreement with previous experimental and theoretical results [62,63], for instant the value of 76.5±8.0 Å 3 by molecular beam deflection technique [64]. According to the calculation, differences in mean polarizabilities of SN-and NBisomers of both target azafullerenes are noticeable.…”
Section: Molecular Electronic Propertiessupporting
confidence: 87%
See 2 more Smart Citations
“…According to these data, all studied structures show great values for static polarizability which is due to many delocalized π-electrons over these molecules. The value of 69.5 Å 3 , calculated at the mentioned level of theory for polarizability of C 60 fullerene, is in satisfactory agreement with previous experimental and theoretical results [62,63], for instant the value of 76.5±8.0 Å 3 by molecular beam deflection technique [64]. According to the calculation, differences in mean polarizabilities of SN-and NBisomers of both target azafullerenes are noticeable.…”
Section: Molecular Electronic Propertiessupporting
confidence: 87%
“…According to the calculation, differences in mean polarizabilities of SN-and NBisomers of both target azafullerenes are noticeable. This is while the previous studies on different exohedral fullerene derivatives (e.g., C 60 (CH 2 ) n and C 60 (NH) n cycloadducts [65]) by Sabirov [63] have shown that mean polarizability of those compounds does not significantly depend on the isomerism. However, for those regioisomeric fullerene bisand multiadducts, differences are observed in anisotropy (a 2 ) of their polarizability [63].…”
Section: Molecular Electronic Propertiesmentioning
confidence: 58%
See 1 more Smart Citation
“…24 In contrast to what is often believed, 25 dispersive and not electrostatic effects seem to be the major stabilizing factor in π−π and C−H−π interactions. 26 Substituent effects in π stacking can be explained solely in terms of direct interactions with the substituents.…”
Section: Stacking and Dispersive Interactions In Selected Supramolecumentioning
confidence: 88%
“…The optically generated dipoles have been estimated by calculating the dipole-moment change from ground state to excited state 13, 15 -17 . It should be pointed out that the widely used acceptor molecules of fullerene derivatives possess very high polarizabilities in exposure to an electric field 18,19,20 . With the high polarizabilities a photoexcitation can largely polarize the fullerene molecules, leading to optically polarized acceptor molecules.…”
Section: Introductionmentioning
confidence: 99%